Scaling up excellence : getting to more without settling for less - Sutton, Robert I. (Crown Business, 2014)
"In Scaling Up Excellence, bestselling author Bob Sutton and Stanford colleague Huggy Rao tackle the topic that obsesses businesses large and small, from start-ups to Fortune 500 companies--how to scale up their businesses and spread excellence throughout the organizational culture"--